2017
DOI: 10.1002/brb3.693
|View full text |Cite|
|
Sign up to set email alerts
|

Childhood trauma and negative memory bias as shared risk factors for psychopathology and comorbidity in a naturalistic psychiatric patient sample

Abstract: BackgroundBoth childhood trauma and negative memory bias are associated with the onset and severity level of several psychiatric disorders, such as depression and anxiety disorders. Studies on these risk factors, however, generally use homogeneous noncomorbid samples. Hence, studies in naturalistic psychiatric samples are lacking. Moreover, we know little about the quantitative relationship between the frequency of traumatic childhood events, strength of memory bias and number of comorbid psychiatric disorders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 47 publications
(74 reference statements)
2
25
0
1
Order By: Relevance
“…Recent evidence from a large naturalistic psychiatric cohort suggests that negative memory bias may be a cognitive marker for a broad range of mental disorders, including ADHD (Vrijsen et al 2017 ). Importantly, the association of Childhood Trauma, negative memory bias, and psychiatric problems remained when excluding depressed patients from the analyses, for which the link with bias had earlier been shown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent evidence from a large naturalistic psychiatric cohort suggests that negative memory bias may be a cognitive marker for a broad range of mental disorders, including ADHD (Vrijsen et al 2017 ). Importantly, the association of Childhood Trauma, negative memory bias, and psychiatric problems remained when excluding depressed patients from the analyses, for which the link with bias had earlier been shown.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, Childhood Trauma (early life stress) and recent stressful events (recent life stress) were both association with ADHD symptom severity. Because both the presence as well as the diversity of stressful events has been related to psychopathology (Hovens et al 2010 ; Vrijsen et al 2017 ), we used variables representing the number of events. We also explored the association between life events and inattention and hyperactivity/impulsivity symptom clusters separately.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with a variety of mental disorders often report CEs [32][33][34][35][36][37][38][39][40][41][42][43]. In our previous study [17], patients with mood disorders reported CEs more often than non-psychiatric individuals investigated in an earlier study [61].…”
Section: Tablementioning
confidence: 96%
“…The investigation was undertaken with a relatively large and representative sample of mood disorder patients recruited from specialized psychiatric care, and extensive data of self-reported symptoms and experiences was collected. Moreover, we examined a comprehensive set of self-reported data of CEs, an important factor in the aetiology of mood disorders, psychosis and BPD [32][33][34][35][36][37][38][39][40].…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation